P439 Insurance coverage, financial strain, and adherence to pre-exposure prophylaxis among gay/bisexual men in the united states. (14th July 2019) - Wray, Tyler; Chan, Phillip
Abstract : Background: Pre-exposure prophylaxis (PrEP) is highly effective in preventing HIV infection, but many at-risk patients have difficulty adhering to the drug over time. Past studies suggest that financial factors, including health insurance coverage, high out-of-pocket expenses, and more general financial strain, may be key factors in PrEP care utilization particularly in the United States, where PrEP is not covered by all insurance plans. However, to date, few studies have explored whether these factors co-occur with disruptions in adherence that are long enough to reduce PrEP's effectiveness. Methods: We recruited 40 PrEP-experienced patients from a sexual health clinic in the northeastern US and instructed them to dispense their PrEP from an internet-connected pill bottle over a 6-month study period. During the study period, participants were also asked to complete monthly surveys assessing insurance coverage, type, and financial strain. Results: GEE models showed that the odds of having a lapse in PrEP adherence of 3+ days were also nearly three times higher in months when participants had incomplete insurance coverage ( OR =2.94, p <0.001) and the rate of lapse days was five times higher ( IRR =5.00, p < 0.001). Participants also had significantly higher percent adherent days (β=0.23, p =0.003) and lapse days occurred nearly four times less often ( IRR =0.27, p <0.001) in months they were insured with Medicaid, versus individual- or employer-provided plans. Finally, the odds of experiencing a significant lapse in adherence was about two times higher ( OR =1.77, p =0.049) and lapse days occurred significantly more frequently ( IRR =1.38, p <0.001) in high financial strain months. Conclusion: Our results suggest that insurance coverage plays a vital role in ensuring patients maintain protective levels of PrEP over time. Although having any coverage is critical, our findings also show that those with private insurance may have more difficulty adhering to PrEP at protective levels, possibly due to restrictions these providers place on obtaining PrEP. Disclosure: No significant relationships.